fMLP-Induced IL-8 Release Is Dependent on NADPH Oxidase in Human Neutrophils - María A. Hidalgo; María D. Carretta; Stefanie E. Teuber; Cristian Zárate; Leonardo Cárcamo; Ilona I. Concha; Rafael A. Burgos (Journal of Immunology Research)
N-Formyl-methionyl-leucyl-phenylalanine (fMLP) and platelet-activating factor (PAF) induce similar intracellular signalling profiles; but only fMLP induces interleukin-8 (IL-8) release and nicotinamide adenine dinucleotide phosphate reduced (NADPH) oxidase activity in neutrophils. Because the role of ROS on IL-8 release in neutrophils is until now controversial, we assessed if NADPH oxidase is involved in the IL-8 secretions and PI3K/Akt, MAPK, and NF-κB pathways activity induced by fMLP. Neutrophils were obtained from healthy volunteers. IL-8 was measured by ELISA, IL-8 mRNA by qPCR, and ROS production by luminol-amplified chemiluminescence, reduction of ferricytochrome c, and FACS. Intracellular pH changes were detected by spectrofluorescence. ERK1/2, p38 MAPK, and Akt phosphorylation were analysed by immunoblotting and NF-κB was analysed by immunocytochemistry. Hydroxy-3-methoxyaceto-phenone (HMAP), diphenyleneiodonium (DPI), and siRNA Nox2 reduced the ROS and IL-8 release in neutrophils treated with fMLP. HMAP, DPI, and amiloride (a Na+/H+ exchanger inhibitor) inhibited the Akt phosphorylation and did not affect the p38 MAPK and ERK1/2 activity. DPI and HMAP reduced NF-κB translocation induced by fMLP. We showed that IL-8 release induced by fMLP is dependent on NADPH oxidase, and ROS could play a redundant role in cell signalling, ultimately activating the PI3K/Akt and NF-κB pathways in neutrophils.